2015
DOI: 10.4103/0366-6999.168048
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Transthyretin Amyloidosis in Eight Chinese Families

Abstract: Background:Mutations of transthyretin (TTR) cause the most common type of autosomal-dominant hereditary systemic amyloidosis, which occurs worldwide. To date, more and more mutations in the TTR gene have been reported. Some variations in the clinical presentation are often observed in patients with the same mutation or the patients in the same family. The purpose of this study was to find out the clinicopathologic and genetic features of Chinese patients with hereditary TTR amyloidosis.Methods:Clinical and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
4
14
1
Order By: Relevance
“…Published estimates for the timing of disease milestones are heavily influenced by patients with Portuguese-type Val30Met disease in endemic countries, which is the most prevalent form and for which onset is typically at 30–40 years old [15], and generally onset is earlier in endemic versus non-endemic countries (except in Sweden where it is typically late-onset). Furthermore, previous case series have reported that age of onset is later for non-Val30Met ATTR-PN [21, 22]. Thus, the later onset reported here appears consistent with the aforementioned trends given that cases were predominantly from non-endemic countries and non-Val30Met (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Published estimates for the timing of disease milestones are heavily influenced by patients with Portuguese-type Val30Met disease in endemic countries, which is the most prevalent form and for which onset is typically at 30–40 years old [15], and generally onset is earlier in endemic versus non-endemic countries (except in Sweden where it is typically late-onset). Furthermore, previous case series have reported that age of onset is later for non-Val30Met ATTR-PN [21, 22]. Thus, the later onset reported here appears consistent with the aforementioned trends given that cases were predominantly from non-endemic countries and non-Val30Met (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Untreated disease results in inexorably progressive symptoms with devastating effect on quality of life and reduced survival at 5 to 15 years from the onset of symptoms. ATTRm amyloid deposits within the vitreous causing blindness and the leptomeninges with CNS deficits are also recognized (Connors et al., ; Holmgren, Hellman, Lundgren, Sandgren, & Suhr, ; Long et al., ; Meng et al., ; Uemichi, Uitti, Koeppen, Donat, & Benson, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, TTR‐FAP is now believed to have worldwide distribution (Benson and Kincaid, ) . More and more TTR‐FAP patients in Han Chinese people have been reported (Table ) (Yamamoto et al , ; Chou et al , ; Lachmann et al , ; Li et al , , ; Lim et al , ; Mak et al , , ; Liu et al , , , ; Yang et al , ; Chen et al , ; Zhang et al , , ; Long et al , ; Zou et al , ; Lv et al , ; Meng et al , ) . Here, we identified four different TTR heterozygous mutations already known to be associated with FAP in four unrelated families and among them, mutations Thr49Ala(p.Thr69Ala) and Tyr116Ser(p.Tyr136Ser) were detected for the first time in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%